Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Nelayan Trawl Di Pesisir Kelurahan Kuala Samboja Kabupaten Kutai Kartanegara. - Radika Nurfatiha; Nurul Ovia Oktawati; Juliani (2339-1324, 2023)
ABSTRACT Fishermen's income is very relatively erratic and depends heavily on the catch obtained after going to sea and the expenditure of the operational costs of the fishing process. This study aims to analyze the influence of fish price factors, catches, operational costs, and education, on the income of fishermen in Kuala Samboja Village, Kutai Kartanegara Regency. The type of research data used in this study is quantitative with primary data sources obtained through interviews using questionnaires. The free variables in this study are fish price (x1), catch (x2), operational costs (x3), and education (x4), and the bound variable (Y) is fishermen's income. The analysis methods used are descriptive statistical analysis, multiple linear regression analysis, hypothesis test, coefficient of determination and classical assumption test using the windows spss 16.0 program. The results of the analysis showed that simultaneously the factors of fish prices, catches, operational costs, and education showed a significant effect on fishermen's income. It partially showed that catch factors (0.030) and operating cost factors (0,003) had a significant effect on fishermen's income, while fish price factors (0,033) and education (0.097) did not have a significant effect on fishermen's income. The highest influence on fishermen's income in Kuala Samboja Village, Kutai Kartanegara Regency, is the catch factor with a calculated t-test value of 3,304 > 2045.